MIND OVER SPEECH: THE ROLE OF ANXIETY IN EFL STUDENTS’ ORAL PRESENTATION PERFORMANCE - Aysha Almagsodi (Institut Agama Islam Negeri Bone, 2025)
Oral presentation is a crucial academic and professional skill that reflects communicative competence and self-confidence, yet it remains one of the main sources of anxiety among English as a Foreign Language (EFL) learners. Despite extensive research on speaking anxiety, limited attention has been given to the specific demands of oral presentations, where students must perform under evaluation and linguistic pressure. This study aimed to examine the role of anxiety in EFL students’ oral presentation performance, focusing on Saudi female undergraduates at King Khalid University. A quantitative descriptive design was adopted, and data were collected through a validated questionnaire administered to thirty students in the Department of English. The instrument, showing high reliability (Cronbach’s α = 0.81), measured four dimensions: psychological, linguistic, situational, and preparation-related factors. Descriptive statistical analysis using SPSS revealed that psychological anxiety was the most influential variable, followed by preparation and linguistic limitations. Participants reported shyness, fear of mistakes, and concern over negative evaluation as key stressors. Although structured rehearsal improved confidence, overreliance on memorization increased tension. The findings highlight that effective oral performance depends on both linguistic ability and psychological readiness. The study concludes that integrating anxiety-reduction strategies, reflective practice, and confidence-building training within EFL curricula can enhance learners’ oral communication skills and overall performance.